Dittos: Personalized, Embodied Agents That Participate in Meetings When You Are Unavailable - Leong, Joanne; Tang, John; Cutrell, Ed; Junuzovic, Sasa; Baribault, Gregory Paul; Inkpen, Kori (2024 Conference on Computer Supported Cooperative Work, 2024)
Imagine being able to send a personalized embodied agent to meetings you are unable to attend. This paper explores the idea of a Ditto—an agent that visually resembles a person, sounds like them, possesses knowledge about them, and can represent them in meetings. This paper reports on results from two empirical investigations: 1) focus group sessions with six groups (n=24) and 2) a Wizard of Oz (WOz) study with 10 groups (n=39) recruited from within a large technology company. Results from the focus group sessions provide insights on what contexts are appropriate for Dittos, and issues around social acceptability and representation risk. The focus group results also provide feedback on visual design characteristics for Dittos. In the WOz study, teams participated in meetings with two different embodied agents: a Ditto and a Delegate (an agent which did not resemble the absent person). Insights from this research demonstrate the impact these embodied agents can have in meetings and highlight that Dittos in particular show promise in evoking feelings of presence and trust, as well as informing decision making. These results also highlight issues related to relationship dynamics such as maintaining social etiquette, managing one’s professional reputation, and upholding accountability. Overall, our investigation provides early evidence that Dittos could be beneficial to represent users when they are unable to be present but also outlines many factors that need to be carefully considered to successfully realize this vision.